Preparation of ultrafine iron particles by chemical vapor deposition of Fe(CO) sub 5. Fe(CO) sub 5 wo gebryo to suru kiso kagaku hanno ni yoru tetsuchobiryushi no seisei - "Sawada, Y"; "Kageyama, Y. (Mitsubishi Petrochemical Co. Ltd., Tokyo (Japan)): Iwata, M. (Nagoya University, Nagoya (Japan). Faculty of Engineering)" (1991)
An ultrafine iron particle preparing process was developed, which wses gaseous phase pyrolysis in magnetic field of iron pentacarbonyl, Fe(CO){sub 5}, based on the fact that Fe(CO){sub 5} has peculiar characters that its boiling point is as low as 103degreeC, and starts decomposing in a low temperature zone of 100degreeC or lower. Vaporizing and introducing into a reactor an fe(CO){sub 5}, andPyrolyzing it at 200-600degreeC while being diluted with nitrogen and applied with a magnetic field produced uitrafine iron particles of a necklace-like chain comprisinh primary particles having diameter of 15 to 25 nm with 10 to 40 of them linked in a straight chain. It was found that the specific surface area is 30-50 msup 2/g, with the diameter converted from the specific surface area being relatively close to the average diameter obtained from TEM photograph, and that the particle has few pores. Magnetically the iron powder has a coercivity of 123-131 KA/m and a specific saturation magnetization of 120-140 Amsup 2/kg, and is expected to be applied as a high density magnetic recording medium. 5 refs.,8 figs., 3 tabs.
Keywords: "36 MATERIALS SCIENCE"; "37 INORGANIC, ORGANIC, PHYSICAL AND ANALYTICAL CHEMISTRY"; "IRON"; "CARBONYLS"; "DECOMPOSITION"; "VAPORS"; "PARTICULATES"; "CHAINS"; "COERCIVE FORCE"; "PARTICLE SIZE"; "PRODUCTION"; "SURFACE AREA"; "INERT ATMOSPHERE"; "MAGNETIC FIELDS"; "CHEMICAL REACTIONS"; "ELEMENTS"; "FLUIDS"; "GASES"; "METALS"; "PARTICLES"; "SIZE"; "SURFACE PROPERTIES"; "TRANSITION ELEMENTS"; "360101* - Metals & Alloys- Preparation & Fabrication"; "400800 - Combustion, Pyrolysis, & High-Temperature Chemistry"